1986
DOI: 10.1055/s-0038-1661563
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of the Contact Phase of Blood Coagulation in the Adult Respiratory Distress Syndrome (ARDS)

Abstract: SummaryIn order to assess the role of the kallikrein-kinin (K-K) system in the pathogenesis of the adult respiratory distress syndrome (ARDS) we have prospectively determined coagulation contact phase, blood gas and hemodynamic parameters in patients with ARDS at 0, 36 and 72 h from diagnosis.Compared to normal values, significantly lower mean levels of factor XII (71.4 ± 9.8%, p <0.0005), prekallikrein (PPK) (52 ± 5.7%, p <0.0005), high molecular weight kininogen (HMWK) (73 ± 2%, p <0.0005) and α2-ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…This decrease could not be attributed to hemodilution in that the hematocrit increased moderately during the experiment and the increase was similar in both groups (data not shown). Previous studies by us and others have shown that, in ARDS patients, the plasma levels of HK, factor XII, and PK were decreased suggesting an activation of the kallikrein-kinin system (29,30). In our study (29), the decrease in PK levels correlated with the severity of the pulmonary dysfunction; conversely, in patients with pulmonary dysfunction due to cardiogenic pulmonary edema without ARDS, the plasma levels of PK, factor XII, and high molecular weight kininogen were not decreased.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…This decrease could not be attributed to hemodilution in that the hematocrit increased moderately during the experiment and the increase was similar in both groups (data not shown). Previous studies by us and others have shown that, in ARDS patients, the plasma levels of HK, factor XII, and PK were decreased suggesting an activation of the kallikrein-kinin system (29,30). In our study (29), the decrease in PK levels correlated with the severity of the pulmonary dysfunction; conversely, in patients with pulmonary dysfunction due to cardiogenic pulmonary edema without ARDS, the plasma levels of PK, factor XII, and high molecular weight kininogen were not decreased.…”
Section: Discussionmentioning
confidence: 85%
“…Previous studies by us and others have shown that, in ARDS patients, the plasma levels of HK, factor XII, and PK were decreased suggesting an activation of the kallikrein-kinin system (29,30). In our study (29), the decrease in PK levels correlated with the severity of the pulmonary dysfunction; conversely, in patients with pulmonary dysfunction due to cardiogenic pulmonary edema without ARDS, the plasma levels of PK, factor XII, and high molecular weight kininogen were not decreased. Thus, it appears that in ARDS the activation ofthe contact system is not a direct consequence of the pulmonary edema (3 1 ).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The usual postperfusion syndromes can then appear, with their escalating possibilities, even continuing to sepsis, ARDS or MOF. [5][6][7][8]23 In light of this relationship, the value of improving the artificial materials' biocompatibility as a means to controlling these syndromes has long been recognized. As the first heparin-coated oxygenators became available in the last half of the 1980s, many research groups examined the oxygenators' biocompatibility in in vitro systems, animal models, and later, in patient studies.…”
Section: Discussionmentioning
confidence: 99%
“…This syndrome can lead to systemic inflammatory response syndrome (SIRS), acute lung failure (ARDS, adult respiratory distress syndrome), sepsis and multi-organ failure (MOF). [5][6][7][8][9] The incomplete haemocompatibility of the perfusion systems used during ECC plays a significant role in these changes. Therefore, in paediatric cardiac surgery, minimization of the CPB-mediated activation mechanisms caused by the interactions of the blood with the artificial surfaces are of prime importance.…”
Section: Introductionmentioning
confidence: 99%